Impact of organophosphate pesticides exposure on human semen parameters and testosterone: a systematic review and meta-analysis - Hamed, Moses A.; Akhigbe, Tunmise M.; Adeogun, Adetomiwa E.; Adesoye, Oluwatosin B.; Akhigbe, Roland E. (Frontiers in Endocrinology, 2023)
Background: Organophosphate (OP) pesticides have been associated with a decline in semen quality, although there are still considerable arguments about the magnitude of the association.Objective: This study provides a systematic review and meta-analysis of the impacts of OP pesticides on semen quality and male reproductive hormones.: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols. Strategic search was conducted using combined text words as search terms. The eligibility criteria were developed based on Population, Exposure, Comparator, Outcome, and Study designs (PECOS) framework. Relevant data were extracted, risk of bias was evaluated by The Office of Health Assessment and Translation (OHAT) tool, and certainty of evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Working Group guidelines. Quantitative meta-analysis was performed by using Review Manager.Results: A total of 766 male subjects (349 exposed to OP pesticides and 417 unexposed controls) were included in the meta-analysis. There was no significant difference in the ejaculate volume, seminal fluid volume, sperm multiple anomaly index, sperm, and leukocytes levels of the OPexposed subjects compared to the control. In addition, OP pesticides exposure did not significantly affect serum concentrations of FSH, LH, and testosterone in subjects who were exposed to OP pesticides compared to their unexposed counterparts. However, we found a significant reduction in the sperm count, sperm concentration, progressive sperm motility, total sperm motility, and normal sperm morphology of OP pesticides-exposed subjects compared to the unexposed subjects. However, after subtype and sensitivity analyses, exposure to OP pesticides did not reduce sperm count. Also, after sensitivity analysis, OP pesticides exposure did not alter progressive sperm motility.Conclusions: This study demonstrates that OP pesticides exposure reduced sperm count, concentration, total and progressive motility, and normal sperm morphology, possibly via a testosterone-independent mechanism.